2019
DOI: 10.20986/resed.2019.3686/2018
|View full text |Cite
|
Sign up to set email alerts
|

Anestesia y analgesia epidural cervical para cirugía de miembro superior

Abstract: Introduction: Cervical epidural anesthesia has been successfully used for various types of surgical procedures involving upper limb surgery, thoracic wall surgery, carotid artery surgery and neck dissections, keeping the patient conscious, with less blood loss and a surgical fi eld more bloodless, also presents lower failure rate, lower total dose of local anesthesia and maintenance of postoperative analgesia through a catheter. Objective: To describe anesthetic management and postoperative analgesia in a pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…In a series of cases with clavicle fracture undergoing open reduction and internal fixation under analgesia by block of the pectoral nerves suggests that for this type of intervention loco-regional methods of anesthesia such as paravertebral, epidural or terminal branch blocks are more effective and safer compared to endotracheal general anesthesia. Vela-Izquierdo et al [7].identified that in upper limb and shoulder girdle surgery, postoperative analgesia by epidural catheter in continuous infusion using local anesthetics block the entry of nociceptive stimuli into the central nervous system and the addition of opioids brings a synergistic effect and a potentiation of analgesia, reducing postoperative pain, cardiovascular, pulmonary, infectious, gastrointestinal complications and the need for complementary analgesia with opioids, improving patient satisfaction. In this work it was also identified that heart rate and mean arterial pressure followed a Gaussian distribution at 30 and 60 min after the start of cervical epidural block, this means that most of the values were close to the median, while there were extreme values less frequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of cases with clavicle fracture undergoing open reduction and internal fixation under analgesia by block of the pectoral nerves suggests that for this type of intervention loco-regional methods of anesthesia such as paravertebral, epidural or terminal branch blocks are more effective and safer compared to endotracheal general anesthesia. Vela-Izquierdo et al [7].identified that in upper limb and shoulder girdle surgery, postoperative analgesia by epidural catheter in continuous infusion using local anesthetics block the entry of nociceptive stimuli into the central nervous system and the addition of opioids brings a synergistic effect and a potentiation of analgesia, reducing postoperative pain, cardiovascular, pulmonary, infectious, gastrointestinal complications and the need for complementary analgesia with opioids, improving patient satisfaction. In this work it was also identified that heart rate and mean arterial pressure followed a Gaussian distribution at 30 and 60 min after the start of cervical epidural block, this means that most of the values were close to the median, while there were extreme values less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…lower limb surgery [6]. upper limb and shoulder girdle surgery and thyroid surgery [7,8]. This is because its use allows to avoid in many occasions the use of endotracheal general anesthesia, with all the complications related to the management of the airway and the use of sedatives, neuro-muscular relaxants and opioid analgesics parenterally.…”
Section: Introductionmentioning
confidence: 99%